Answer:
9
Explanation:
The first thing to do is to subtract 16 from both side of the equation:
16 - 16 - b = 7 - 16
The 16s on the left cancel out resulting in:
-b = -9
Think of the -b as -1(9). This is multiplication. By doing the inverse operation (division) we can get rid of the negative on the b. We will divide both sides by -1.
![(b)/(-1) = (-9)/(-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/fatuvuobm6y38570ognicdmepmxo4srac1.png)
This leaves a positive b. Since both parts of the right side of the equation are negative it becomes positive ( a negative divided by a negative is a positive).
The final answer is b= 9.
Check our work by plugging in the b value (9) into the original equation:
16 - 9 = 7
7 = 7 is true so we now we have the right answer.